Question Level Analysis based on the Observed Taxonomy of Learning Outcome Structures in the 2013 Elementary School Mathematics Curriculum Book: Analisis Level Pertanyaan berdasarkan Taksonomi Struktur Hasil Belajar yang Diamati pada Buku Matematika Kurikulum 2013 Sekolah Dasar - Uyun, Luluk Muflikhatul; Wardana, Mahardika Darmawan Kusuma (Indonesian Journal of Education Methods Development, 2023)
This study aims to describe the level of questions on math story problems in the 2013 curriculum book by calculating the percentage of each level of Unistructural, Multistructural, Relational, and Expanded Abstract. This study uses a qualitative approach with a check list method. The SOLO taxonomy is an evaluation tool to determine the quality of the response to a problem. The results of this study contained 230 questions overall and 32 questions SOLO Taxonomy. Unistructural question level percentage 6.24% SOLO Taxonomy questions. The percentage at the level of Multistructural questions is 3.24%, while at the level of relational questions is 90.62%, and the percentage at Expanded Abstract is 0%. From the results of the data obtained, it appears that at the level of the Relational question has the highest percentage with a result of 90.62%. This shows that the 2013 curriculum fifth grade mathematics book is in accordance with the theory of SOLO Taxonomy.